The Application of Information Gap Activities to Improve the Speaking Skill of the Second Year Students of SMA Tri Bhakti Pekanbaru - Ria Oktariska Oktariska; Marzuki '; Mahsyur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This classroom action research was aimed to find out if the application of information gap activities technique could improve the speking skill of the second year students of SMA Tri Bhakti Pekanbaru.. The participants were 28 students. The procedures applied were: (a) giving explanation about the activity or the way of what students should do in the class, (b) reviewing vocabularies used based on the context, (c) giving the texts that consisted of information gap that had been prepared for the students, (d) asking the students to work in pair to complete the task and communicate with other students to get the complete information, (e) asking the students to describe the results of their discussion with their partners. The data was collected by using of observations, tests, and field notes. The research finding showed that the implementation of applying information gap as the teaching technique could improve students’ speaking ability both at the first cycle and second cycle. The finding also proved that in the pre-test students’ average score was only 45.05 and it improved to 73.31 in the post-test 1, and finally improved to 81.33 in the post-test 2. It was also proved that applying the procedures of information gap technique in teaching speaking could raise students’ interest and motivation to speak and share ideas with their partnersin pairs or groups since the core of information gap was a collaboration between groups or pairs. In addition, applying information gap as a teaching technique in English language teaching and learning could also improve students’ ability to speak English in terms of grammar, vocabulary, pronunciation, fluency, and comprehension.Keywords: Information gap activities , Students’ speaking Ability, Spoof Text